Análise ambiental da microbacia hidrográfica do Ribeirão Ema, Rolândia-PR - Piccole, Eduardo Mattos de (2025)
Water resources play a crucial role in maintaining life, economic development, and social well-being, being necessary for a wide variety of uses such as public supply, agriculture, energy generation, and navigation. However, the disorderly exploitation of these resources has led to water scarcity and contamination, primarily due to improper disposal of effluents and the lack of basic sanitation. The absence of sewage treatment and increasing urbanization further compromise water quality and public health. In rural areas, difficulties in providing adequate supply and sanitation services are exacerbated by population dispersion and lack of infrastructure. Monitoring water quality is essential for identifying environmental impacts and preserving water bodies. This study aimed to analyze the micro-basin of the Ribeirão Ema in Rolândia (PR) in order to understand the environmental conditions of the region and identify challenges for the sustainable management of local water resources. To analyze the quality indicators related to the chemical and physical parameters of the Ribeirão Ema micro-basin, semi-annual reports from tests conducted by the Paraná Sanitation Company, in accordance with the NBR ISO/IEC 17025 standard, were used and entered into the public database of the Water Quality Surveillance Information System for Human Consumption - Sisagua, provided by the Ministry of Health. Based on the data accessed from Sisagua, it was found that the concentrations of phosphorus, ammoniacal nitrogen, nitrite, and nitrate remained below the limit established by CONAMA 357/2005 in all analyzed periods, and the pH of the samples was within the recommended range. In the microbiological parameter quantification, the presence of Escherichia coli was detected in all collections, with a high concentration of 6867 MPN/100mL recorded in August 2022. According to the data consulted in Sisagua, no contaminants metals were found in the analyses of the samples collected from the Ribeirão Ema.